The characterization of asphaltene behavior in some aromatic solvents by dynamic nuclear polarization technique - Peksoz, A.; Almaz, E.; Yalçıner, A. (My University, 2010)
Dynamic nuclear polarization (DNP) studies of asphaltene/some hydrocarbons solutions were performed at 1.53. mT. The low field EPR spectrum of Asphaltene/Mesitylene sample was recorded. The DNP parameters such as enhancement factor, nuclear-electron coupling constant, saturation factor, leakage factor, the parameter for the relative importance of scalar and translational dipolar interaction and the total spin-lattice relaxation rate were determined. The effect of irradiation with neutrons from the Ra-Be source to the DNP parameters was investigated. Dissolved molecular oxygen effect on the enhancement factor for each sample was examined experimentally. We also make some interpretations depending on the results obtained for the interactions between nuclei of the solvent and electrons delocalized on the asphaltene. © 2010 Elsevier B.V.
Keywords: Asphaltene; Asphaltene oxidation; Dynamic nuclear polarization; Oximetry; Proton-electron double resonance